Could loneliness accelerate the progression of diabetes among adults with prediabetes: national longitudinal cohort - Weiwei Wang; Feifei Lin; Chen Zhang; Xiaotian Chang; Gang Wang; Lei Feng (BMC Public Health)
Abstract Background Loneliness was associated with an elevated risk of diabetes among initially healthy people in recent studies, whether this association remains among individuals with prediabetes is unknown. This study aimed to assess the longitudinal association between loneliness and progression from prediabetes to diabetes, and whether restless sleep could mediate the potential association. Methods This study used data of 4,296 adults with prediabetes from the China Health and Retirement Longitudinal Study (CHARLS), a national community-based cohort from 2011 to 2020. Loneliness was measured by a 4-point question derived from the Centre for Epidemiological Studies Depression Scale. The outcome was incident diabetes identified by a self-reported diabetes diagnosis or treatment with glucose-lowering medication. Interval-censored Cox regression models were used to investigate the associations and generalized structural equations models were used to estimate the mediation effect. Covariates included baseline age, sex, education, marriage, insurance, living area, smoking, drinking, physical activity, BMI, handgrip strength, social activity, dyslipidemia, hypertension, lipid-lowering drugs, antihypertensive agents, renal or hepatic impairment, and baseline HbA1c level. Results A total of 4,296 participants were included in this study. During a median follow-up period of 9 years, 658 (15.3%) diabetes were observed with an incidence rate of 19.8 per 1,000 person-years among the overall prediabetic participants. Loneliness was associated with a 26% higher risk of transition to diabetes (loneliness vs. non-loneliness: adjusted hazard ratio 1.26, 95% CI 1.05–1.52). Participants who experienced loneliness most frequently (5–7 days per week) had a 1.53-fold higher risk of incident diabetes (95% CI: 1.13–2.07) compared with those without feeling lonely. The association between loneliness and prediabetes progression was mediated by restless sleep. Conclusions Loneliness was independently associated with a higher hazard of progression from prediabetes to diabetes among middle-aged and older adults. Intervention on reducing the frequency of loneliness among the prediabetic population is warranted.